Chironomid species counts and chironomid-inferred summer temperatures, Lake N14, Greenland (early Holocene and late glacial) (2022) - Yarrow Axford; Andrew Medeiros; Peter Puleo; Grace Schellinger; Regan Steigleder; Sarah Woodroffe (Arctic Data Center, 2022)
This dataset contains subfossil chironomid (Diptera: Chironomidae) species counts and the corresponding chironomid-inferred summer temperatures from a sediment core recovered from Lake N14 in southern Greenland. The record covers the period from approximately 13,800 to 9,900 years ago (cal BP). These data were generated for the study named below, which should be consulted for details and cited when using these data. Medeiros, A.S., Chipman, M., Francis, D.R., Hamerlik, L., Langdon, P., Puleo, P.J.K., Schellinger, G., Steigleder, R., Walker, I.R., Woodroffe, S., and Axford, Y. 2022. A continent-scale chironomid training set for reconstructing arctic temperatures. Quaternary Science Reviews 294, 107728. DOI 10.1016/j.quascirev.2022.107728.